2021
DOI: 10.7717/peerj.11034
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Attitudes towards Medical Communication Scale in nursing students

Abstract: Background Adequate communication skills in healthcare professionals are one of the key elements required for achieving high-quality healthcare. Thus, measurement instruments able to assess the dimensions related to these skills, including attitudes towards communication, are useful and convenient tools. Objectives To (a) cross-culturally adapt and validate a scale to measure attitudes towards communication in a sample of nursing students i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The attitudes towards communication were evaluated using the Spanish version ( Attitudes Towards Health Communication [ 37 ]) of the Attitudes Towards Medical Communication Scale [ 38 ]. This one-dimensional instrument comprises 11 assessable items measured on a 5-option Likert-type response scale from “strongly disagree” (1) to “strongly agree” (5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The attitudes towards communication were evaluated using the Spanish version ( Attitudes Towards Health Communication [ 37 ]) of the Attitudes Towards Medical Communication Scale [ 38 ]. This one-dimensional instrument comprises 11 assessable items measured on a 5-option Likert-type response scale from “strongly disagree” (1) to “strongly agree” (5).…”
Section: Methodsmentioning
confidence: 99%
“…The overall score ranges from 11 to 55 points, with higher scores reflecting more positive attitudes towards communication. The Spanish version of the scale has an adequate internal consistency score of 0.75 [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…In Carbonell -Forniés, et al, 2021). It would be interesting to be able to shed light on whether the simulation programme has had no effect on this particular outcome or whether it is because the stu- Reime et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As suggested, this may be explained by the fact that these students already have a good attitude towards communication, which is most likely linked to previous training received during their nursing studies. In fact, it has been shown that first‐year nursing students start out with a lower attitude towards communication than those in their final year, who have already received specific communication skills training during their course (Escribano, Cabañero‐Martínez, Carbonell‐Forniés, et al, 2021). It would be interesting to be able to shed light on whether the simulation programme has had no effect on this particular outcome or whether it is because the students' attitude levels have reached a plateau.…”
Section: Discussionmentioning
confidence: 99%
“…Items on this one-dimensional scale can be answered on a Likert scale from 1 ("strongly disagree") to 5 ("strongly agree"). The Spanish version of this scale was adapted and psychometrically evaluated in a nursing sample (35). A German version of the ATMCS will be translated using the TRAPD translation protocol (31), and adapted to our target group.…”
Section: Attitudes Towards Medical Communicationmentioning
confidence: 99%